Improving pedestrian access way planning using designing out crime - Love, Terence; Cozens, Paul (Planning and Transport Research Centre (PATREC), 2008)
Pedestrian Access Ways (PAWs) have presented a significant and unresolved challenge to transport planners in local and State government. The result has been piecemeal local government and State government approaches that have frequently resulted in tensions between civic constituencies, high levels of administrative cost, adverse publicity, reduced transport functionality and compromises to the policy intentions of a range of government agencies. In part, this has been due to a gap between the intrinsic complexity of PAW eco-systems and the oversimplification of this complexity in ways that ignores issues of multiple uses, purposes, user interests, user groups, functionality, ownership, control and agency and the ways these vary across the day, week, seasons, years and planning fashions. In short, local interests and incomplete understanding the situation have limited the development of best practice in management of PAWs, have generated unnecessary problems, and in particular have prevented an integrated government approach. This paper presents findings of recent research on the management of PAWs to reduce crime. This required identifying and addressing unresolved and overlooked issues. Outcomes included: a morphology of PAWs and PAW functioning; the identification of information for understanding the functioning of individual PAWs; the discovery of the misapplication of Designing Out Crime techniques to PAWs; the identification of misunderstandings leading to flawed policy actions; the exposure of ways that adverse PAW outcomes are manufactured by planning policies and decisions; proposals for an improved approach to managing PAWs to reduce crime via Designing Out Crime techniques; and, the development of PAW Guidelines as a supplement to the State Designing Out Crime Planning Guidelines for use by local government. The research was funded by the Office of Crime Prevention (OCP) and undertaken by the authors as members of the cross-university Design Out Crime research group.